Tensile and thermal properties of coconut shell powder filled polylactic acid biocomposites - Koay, Seong Chun (School of Materials Engineering, 2012)
In this research the effect of coconut shell powder (CPS) content and chemical modification on mechanical properties, morphology and thermal properties of polylactic acid (PLA/CSP) biocomposites were studied.